Analysis of Procurement and Supply Chain Control of Sugarcane in a Sugar Mill - Erika Aprilia Renata; Teguh Soedarto; Sri Widayanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Sugarcane raw material stocks in sugar factories need to be maintained at an optimal level to avoid either shortage or excess situations that ensuring smooth production. This study aims to analyze the procurement mechanism and inventory control of sugarcane raw materials, analyze the trend of sugarcane raw material procurement, and to analyze the inventory control of sugarcane raw materials. Research was conducted at PT PG Candi Baru Sidoarjo. Data was analyzed using descriptive analysis, trend analysis, and Economic Order Quantity (EOQ) analysis. Results of this study showed the procurement mechanism and inventory control of sugarcane raw materials by PT PG Candi Baru. The trend of sugarcane raw materials had decreased every period caused by several factors. The number of economical sugarcane orders in the last year 2023 was 1,491,545,174 tons. The amount of safety stock that must be owned by PT PG Candi Baru Sidoarjo was 234,044.8 tons. The number of reorder (Reorder Point) was 505,761 tons. The optimal total cost of sugarcane raw material inventory was IDR 20,885,934,920.14, while the company policy was IDR 20,998,060,000. It can be concluded that the EOQ method obtained more efficient results with a financial difference value of IDR 112,125,079.86.